Active, Passive, and Absorptive RIS-Aided 6G Network Under Non-Orthogonal CCI - Volkan Ozduran; Ehsan Soleimani-Nasab; Nikolaos Nomikos; Imran Shafique Ansari; Panagiotis Trakadas (IEEE Open Journal of Vehicular Technology, 2025)
This paper investigates the impact of randomly deployed non-orthogonal co-channel interference (CCI), originating from the information exchange process among non-orthogonal multiple access (NOMA) users, in an active, passive, and absorptive reconfigurable intelligent surface (RIS)-assisted dual-hop network. More specifically, the study considers that the information exchange process involves the source utilizing active, passive, or absorptive RIS architecture, along with a line of sight (LOS)/non-line of sight (NLOS) link between source and destination terminals. Additionally, this study considers the limited non-orthogonal CCI affecting the destination terminal in an independent and identically distributed (i.i.d.) non-orthogonal CCI scenario. Theoretical insights and Monte Carlo-based simulations collectively demonstrate that non-orthogonal CCI severely degrades system performance, particularly in high signal-to-noise ratio conditions, leading to notable losses in system coding gain. Meanwhile, results also reveal that increasing the number of RIS elements stabilizes the system and mitigates the impact of CCI on its performance.